Direct methyl esterification with 2, 2‐dimethoxypropane for the simultaneous determination of urinary metabolites of toluene, xylene, styrene, and ethylbenzene by gas chromatography‐mass spectrometry. Issue 1 (21st January 2019) - Takeuchi, Akito; Namera, Akira; Sakui, Norihiro; Yamamoto, Shinobu; Yamamuro, Kenji; Nishinoiri, Osamu; Endo, Yoko; Endo, Ginji
Abstract: Objectives: The purpose of this study was to develop a simple and accurate gas chromatography‐mass spectrometry (GC‐MS) method for simultaneous determination of four urinary metabolites from four organic solvents, that is, hippuric acid (HA) from toluene, methylhippuric acid (MHA) from xylene, and mandelic acid (MA) and phenylglyoxylic acid (PGA) from styrene or ethylbenzene for biological monitoring. Methods: The four metabolites were directly methyl‐esterified with 2, 2‐dimethoxypropane and analyzed using GC‐MS. The proposed method was validated according to the US Food and Drug Administration guidance. The accuracy of the proposed method was confirmed by analyzing a ClinChek ® —Control for occupational medicine (RECIPE Chemicals +Instruments GmbH). Results: Calibration curves showed linearity in the concentration range of 10‐1000 mg/L for each metabolite, with correlation coefficients >0.999. For each metabolite, the limits of detection and quantification were 3 mg/L and 10 mg/L, respectively. The recovery was 93%‐117%, intraday accuracy, expressed as the deviation from the nominal value, was 92.7%‐103.0%, and intraday precision, expressed as the relative standard deviation (RSD), was 1.3%‐4.7%. Interday accuracy and precision were 93.4%‐104.0% and 1.2%‐9.5%, respectively. The analytical values of ClinChek obtained using the proposed method were sufficiently accurate. Conclusions: The proposed method is a simple and accurate which is suitable for routine analyses that could be used for biological monitoring of occupational exposure to four organic solvents.